2009
DOI: 10.1016/j.neuroscience.2009.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of anxiety and trauma-related disorders

Abstract: Anxiety disorders are the most common psychiatric illnesses in the U.S. with approximately 30% of the population experiencing anxiety-related symptoms in their lifetime (Kessler et al., 2005). Notably, a variety of studies have demonstrated that 30−40% of the variance contributing to these disorders is heritable. In the present review, we discuss the latest findings regarding the genetic and environmental influences on the development and symptomatology of anxiety disorders. Specific emphasis is placed on post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 142 publications
0
50
0
Order By: Relevance
“…Variation in the serotonin transporter gene has been widely studied in association with PTSD [29][30][31] and in particular in the context of gene by environment studies [32][33][34] (see below for further discussion of this type of design). The interested reader is referred to recent reviews of genetic association studies in PTSD for further details [35,36].…”
Section: Gene Association Studies In Ptsdmentioning
confidence: 99%
“…Variation in the serotonin transporter gene has been widely studied in association with PTSD [29][30][31] and in particular in the context of gene by environment studies [32][33][34] (see below for further discussion of this type of design). The interested reader is referred to recent reviews of genetic association studies in PTSD for further details [35,36].…”
Section: Gene Association Studies In Ptsdmentioning
confidence: 99%
“…Until recently, the genetic contribution to PTSD has been investigated largely via candidate gene association studies (reviewed in Almli et al, 2014;Amstadter et al, 2009;Norrholm and Ressler, 2009). Most research has focused on: (1) the hypothalamic-pituitary-adrenal (HPA) axis, (2) the ascending brainstem locus coeruleus noradrenergic system, and (3) the limbic amygdalar frontal pathway mediating fear processing.…”
Section: Introductionmentioning
confidence: 99%
“…Besides gender differences, there are some risk factors known to be involved in PTSD development, such as biological, psychological vulnerabilities and social factors. There is a small or no evidence regarding genetic factor for the PTSD development [6]. In opposite, Vietnam veterans study showed that psychological stress, such as family instability, was found to be a risk factor for the development of PTSD [7].…”
Section: Ptsd Causesmentioning
confidence: 98%